2010
DOI: 10.1002/cncr.25304
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16 in lymph node metastases of adjuvantly treated stage III colorectal cancer patients identifies poor prognostic subgroups

Abstract: BACKGROUND:The objective of identifying protein biomarkers for patients with stage III and IV colorectal cancer is to improve risk stratification and, thus, to identify patients in the postoperative setting who may benefit from more targeted treatment. The objective of the current study was to determine the prognostic value of 19 protein markers assessed in primary tumors and matched lymph node (LN) metastases from patients with stage III and IV colorectal cancer. METHODS: Matched primary tumors and LN metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…Inactivation of the tumor suppressor p16 INK4A seems to play an important role in tumor progression and dissemination [34]. In accordance to squamous cell carcinomas of other origins, we were able to demonstrate a more aggressive behavior of p16-negative tumors.…”
Section: Discussionsupporting
confidence: 81%
“…Inactivation of the tumor suppressor p16 INK4A seems to play an important role in tumor progression and dissemination [34]. In accordance to squamous cell carcinomas of other origins, we were able to demonstrate a more aggressive behavior of p16-negative tumors.…”
Section: Discussionsupporting
confidence: 81%
“…Expression of many markers in LNM, including thymidylate synthase [24], epidermal growth factor receptor (EGFR) [25] and p16 [26], shows better Similar observations were found in other cancers, for example in breast carcinoma [8].…”
supporting
confidence: 67%
“…Previous studies showed that cell cycle progression led to poor prognosis or liver metastasis due to inactivation of p16 INK4a or p27 KIP1 or to activation of cyclin D2 at the G1/S transition [28,29,30], or due to overexpression of CDC25B acting at the G2/M checkpoint [31]. Like other cell cycle regulatory components, it is likely that decreases in LATS2 expression lead to similar unfavorable outcomes in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%